Mechanical Thrombectomy in Ischemic Stroke With a Medium or Distal Arterial Occlusion - Frédéric Clarençon; Fouzi Bala; Amandine Baptiste; Marco Pasi; Gaultier Marnat; Igor Sibon; Benjamin Gory; Sébastien Richard; Raoul Pop; Valérie Wolff; Cédric Fauché; Matthias Lamy; et al. (JAMA, 2026)
Importance Evidence regarding efficacy and safety of thrombectomy in acute ischemic stroke (AIS) due to medium or distal vessel occlusions (MDVOs) is lacking. Objective To evaluate the benefit of thrombectomy, in addition to medical treatment over medical treatment alone, in patients with an AIS related to a primary and isolated MDVO. Design, Setting, and Participants Randomized clinical trial conducted at 22 stroke centers in France from November 2021 to April 2025, with planned enrollment of 488 patients. The trial has been stopped after the planned interim analysis on the recommendation of the data and safety monitoring board for futility and increased rate of symptomatic intracranial hemorrhage with thrombectomy. Eligible adult patients had an AIS due to a primary MDVO within 8 hours of symptom onset or within 24 hours of last seen well if no hyperintense signal was present on fluid-attenuated inversion recovery imaging. Intervention Thrombectomy in addition to medical treatment (n = 123) or medical treatment alone (n = 121). Main Outcomes and Measures The primary end point was a good clinical outcome at 3 months, defined as a modified Rankin Scale score of 0 to 2, assessed by an independent, blinded assessor. Secondary end points included mortality rate at 3 months and adverse and serious adverse events. Results Of the 244 patients randomized (median age, 75 years [IQR, 67-81]; 56% male; median National Institutes of Health Stroke Scale score, 8 [IQR, 6-12]), 100 of the 123 patients in the thrombectomy group (81%) received thrombectomy and none of the 121 patients in the control group received thrombectomy; 217 (89%) completed follow-up. At 3 months, 72 of 116 patients (62%) in the thrombectomy group had a good clinical outcome vs 81 of 119 patients (68%) in the control group (odds ratio, 0.73 [95% CI, 0.40-1.31]; P = .29; adjusted absolute difference, −6.8% [95% CI, −19.4% to 5.7%]). The incidence of symptomatic intracranial hemorrhages was higher among the 100 patients who actually received thrombectomy than in those who did not (11% vs 3%, P = .008), as was incidence of subarachnoid hemorrhages (13% vs 2%, P < .001) and embolus migration (5% vs 1%, P = .04). Mortality rate did not significantly differ between the 2 groups (6% vs 8%; P = .49). Conclusions and Relevance Thrombectomy did not lead to a higher rate of good clinical outcome at 3 months compared with medical treatment alone in patients with acute ischemic stroke related to an MDVO. Hemorrhagic complications were more frequent after thrombectomy. Trial Registration ClinicalTrials.gov Identifier: NCT05030142